2022
DOI: 10.1186/s12876-022-02281-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic nomogram for gallbladder cancer patients after surgery

Abstract: Background Gallbladder cancer is associated with late diagnosis and poor prognosis. Current study aims to develop a prognostic nomogram for predicting survival of gallbladder cancer patients after surgery. Methods Two large cohorts were included in this analysis. One consisted of 1753 gallbladder cancer patients from the Surveillance, Epidemiology, and End Results (SEER) database, and the other consisted of 239 patients from Shanghai Renji hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In the Cox regression analysis, we identified that the age, primary site, grade, and radiotherapy were independent prognostic factors for CSS in patients with pancreatic MCAC. Age and grade have been found to be independent factors for cancer prognosis in many studies ( 18 20 ). At the primary site, the tumors at the head of pancreas have a better prognosis than those at other sites.…”
Section: Discussionmentioning
confidence: 99%
“…In the Cox regression analysis, we identified that the age, primary site, grade, and radiotherapy were independent prognostic factors for CSS in patients with pancreatic MCAC. Age and grade have been found to be independent factors for cancer prognosis in many studies ( 18 20 ). At the primary site, the tumors at the head of pancreas have a better prognosis than those at other sites.…”
Section: Discussionmentioning
confidence: 99%
“…Written consent was obtained from all the patients involved in the present study. Each patient's age, sex, differentiation, Nevin stage ( 28 ), tumor invasion, regional lymph node metastasis, distant metastasis and histological stage were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Surgery remains a fundamental part of GBC management and is the only potentially curative modality (13). Although many studies have reported some prognostic factors for GBC patients, including age, TNM stage, tumor size, adjuvant therapy, and pathological grade (11,(14)(15)(16)(17), there were little data on the survival benefit of surgery in elderly patients with GBC. This special population was rarely included in randomized controlled trials that exploring the effect of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of surgery for the old population has been discussed, but the results were contradictory (8-10). Several studies have also shown that age is a risk factor for prognosis in patients undergoing surgery for gallbladder cancer (11,12). Thus, whether elderly patients with gallbladder cancer can benefit from surgical treatment or not is a topic worth exploring.…”
Section: Introductionmentioning
confidence: 99%